ANALYSIS THE RELATIONSHIP BETWEEN REGULARITY AND DURATION OF ARV THERAPY WITH CD4 LEVEL IN HIV/ AIDS PATIENTS - Musfirah Ahmad; Nur Wahyuni Munir (JIKP Jurnal Ilmiah Kesehatan PENCERAH, 2019)
The aim of this study was to determine the relationship between tension and duration of ARV administration with CD4 levels in patients with HIV / AIDS. The type of research used is quantitative research with an analytical approach, and a cross sectional study design. The subjects of the study were 78 HIV / AIDS patients at the Jumpandang Baru Health Center in Makassar City who were selected by purposive sampling. Data analysis was performed by correlational methods to assess significance (p), direction (+/-) and correlation strength (r). The research instrument used a questionnaire and CD4 laboratory results. Based on the Spearman’ rho test it was found that there was a positive and weak correlation between regularity and duration of ARV therapy with CD4 levels of HIV / AIDS patients with a value of p <0.05; (r + 0.340 and r + 2.22). That is, the more regular and long time patients to get ARV therapy will be increase the CD4 level of the patients. Antiretroviral Therapy is very effective in increasing CD4 levels or immunity status of patients with HIV / AIDS, so it is recommended that patients be more orderly and patient in undergoing a therapy program and the publick health is more supportive of patients in managing the therapy provided.